IMPROVEMENT EFFORTS VERBAL CREATIVITY THROUGH LEARNING CYCLE (5E) WITH AFFINITY DIAGRAM AT BIOLOGY LEASSON IN CLASS X6 AT SMAN 3 BOYOLALI IN ACADEMIC YEAR 2012/2013. - -, Ismiyatin, Suciati, Harlita (P Biologi FKIP UNS Surakarta, 2015)
This research aims to improve the students verbal creativity in class X6 at SMAN 3 Boyolali in Academic Year 2012/2013 through the application of the Learning Cycle (5E) with Affinity Diagram.The observation result toward the learning process of Biologic study for the Students of class X6 SMAN 3 Boyolali Tahun Ajaran 2012/2013 can bee seen that the learning process is not optimal as it is only dominated by the teacher, the students can no longer get active so the student?s capability of improving the idea and giving the argument is not optimal. It indicates that the student?s verbal creativity does not work well. Based on the problem statement above, it needs to increase the learning process by applying a new model in order to activate the student and the constructivism based itself. Learning cycle (5E) is a process made by syntax: enggagement, exploration, exolanation, elaboration dan evaluation. Because the characteristic of biologic material contains many concepts and problems, for instance ecosystem material, so the learning cycle (5 E) is more effective if guided by Affinity Diagram in which the operation principle is to group the problems.This research was a classroom action research which and performed in three cycles. Each cycle consists of four phases, namely planning, action, observation, and reflection. Data collection was used test techniques and Non Test with instrument by questions item, observation and manual interview. Data validation techniques was used triangulation techniques. Data were analyzed using descriptive techniques.The results of this research showed that an increase of students verbal creativity of in Cycle I, II III, covering the aspects 1) fluency (31.78%, 52.07%, 73.52%), 2) Flexibility (22.40% , 41.02%, 48.44%); 3) Originality (15.12%, 33.92%, 48.24%); 4) Elaboration (12.61%, 21.48%, 33.01% ). The increase of students verbal creativity as a whole when it is categorized was in cycle I with a low category was 50%, medium category was 50% and high categories was 0%, Cycle II in a low category was 35.48%, medium category was 48.39%, and high categories was 16.13%, Cycle III in lower category was 25%, medium category was 50% and high category was 25%. Cycle was stopped in Cycle III because the research target have been achieved. The conclusion of this research describes that application of the Learning Cycle (5E) with Affinity Diagrams can increase students verbal creativity in class X6 SMAN 3 Boyolali in Academic Year 2012/2013. Keywords:_ Learning cycle (5E), affinity diagrams, verbal creativity.